1994
DOI: 10.1007/bf00039535
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a pea (Pisum sativum) seed lipoxygenase promoter by inverse polymerase chain reaction and characterization of its expression in transgenic tobacco

Abstract: Part of the 5'-flanking sequence of a pea (Pisum sativum) lipoxygenase (LOX) gene was cloned, after amplification from genomic DNA by inverse polymerase chain reaction. Translational and transcriptional fusions of 818 bp of the 5'-flanking region and its deletion derivatives (-513 and -356) were made to a beta-glucuronidase (GUS)-coding sequence and introduced into tobacco. Analysis of T1 transformants showed that the 818 bp 5'-flanking sequence drove GUS expression in seeds that was temporally regulated in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Mutations in the RY elements led to a decrease in the seed‐specific expression and an increase in expression in leaves, suggesting that the RY elements repress expression in leaves. Forster et al . (1994) have shown that deletion of a region of the pea lipoxygenase ( lox‐2 ) gene promoter that includes an RY element led to an increase in leaf expression, and hence ascribed a downregulatory role for the RY element in non‐seed tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the RY elements led to a decrease in the seed‐specific expression and an increase in expression in leaves, suggesting that the RY elements repress expression in leaves. Forster et al . (1994) have shown that deletion of a region of the pea lipoxygenase ( lox‐2 ) gene promoter that includes an RY element led to an increase in leaf expression, and hence ascribed a downregulatory role for the RY element in non‐seed tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the RY elements led to a decrease in the seed-specific expression and an increase in expression in leaves, suggesting that the RY elements repress expression in leaves. Forster et al (1994) have shown that deletion of a region of the pea lipoxygenase (lox-2) gene promoter that includes an RY element led to an increase in leaf expression, and hence ascribed a downregulatory role for the RY element in non-seed tissues. Investigation of various regions of the usp (unknown seed protein) promoter showed that elimination of an RY element led to threefold increase in seed-specific activity of the promoter, further implicating a negative role to the RY element (Fiedler et al, 1993).…”
Section: Necessary Redundant and Discrete Functions Of The Ry Elementsmentioning
confidence: 99%
“…Inverse PCR is a convenient and versatile method of cloning unknown sequences upstream or downstream of known sequences (Triglia et al 1988). Inverse PCR circumvents the laborious procedures of producing and screening genomic libraries (Forster et al 1994). Nucleotide sequences flanking the NBS sequence have been previously isolated using IPCR in lettuce (Shen et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Inverse PCR circumvents the laborious procedures of producing and screening genomic libraries (Forster et al, 1994). It has successfully been used to isolate the seed lipoxygenase promoter from pea as well as a wound-inducible promoter from asparagus (Forster et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…An additional problem with Inverse PCR is the inefficient PCR amplification of closed circular double-stranded DNA. Forster et al (1994) found that digestion of the self-ligated DNA improved the yields of PCR amplification product. The presence of introns in the target gene must also be considered when carrying out Inverse PCR from genomic DNA.…”
Section: Discussionmentioning
confidence: 99%